Precise location measurement in indoor and outdoor performance sports - Perrat, Bertrand (2017)
Knowing precisely where an athlete is with regards to their environment and the motions involved is of critical interest from a sport performance perspective. Engineering and technology provide a significant opportunity for sport science to achieve this. The research investigates and develops state-of-the-art positioning technologies and techniques to be used for such sport tracking applications. Further addressing the real-world use of such techniques, the thesis additionally focuses on the development of sport specific metrics from such tracking data that can be used for performance analysis. Two separate case studies have supported this research, the first one focusing on precise location measurement indoors, the second one outdoors. Each case study has a targeted sport application.